LED Control System Using Arduino Wemos D1 R1 Based on Web Server Communication Via Internet of Things (IoT) - Sukarman Purba; Mifzal Hariri; Rejeki Jenius Banjarnahor; Sofiana Natalia Siregar (Formosa Journal of Science and Technology, 2023)
The Internet of Things (IoT) is a concept that connects physical devices to an Internet network, enabling data exchange and remote control. In this study, an LED control system was developed using the Arduino Wemos D1 R1, which is based on communication via a web server using IoT. This system uses a web server as a user interface to remotely control the LEDs. Users can access the web server via internet-connected devices, such as smartphones or laptops. They can set the LED status (on or off) by clicking the button provided on the web server interface. This research can be used as a basis for developing other device control systems using the Arduino Wemos D1 R1 and the IoT concept. In further development, this system can be improved by adding sensors or other additional features for more complex applications.